2006
DOI: 10.2337/diacare.29.02.06.dc05-1572
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness and Net Benefit of Enhanced Treatment of Depression for Older Adults With Diabetes and Depression

Abstract: OBJECTIVE -To determine the incremental cost-effectiveness and net benefit of a depression collaborative care program compared with usual care for patients with diabetes and depression. RESEARCH DESIGN AND METHODS-This article describes a preplanned subgroup analysis of patients with diabetes from the Improving Mood-Promoting Access to Collaborative (IMPACT) randomized controlled trial. The setting for the study included 18 primary care clinics from eight health care organizations in five states. A total of 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
184
1
9

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(197 citation statements)
references
References 39 publications
3
184
1
9
Order By: Relevance
“…The ADA recommends depression assessment and treatments into routine diabetes care [3]. Randomized clinical trials have demonstrated that the integrated management of type 2 diabetes and depression could improve both medication adherence and symptoms of diabetes and depression [28], and screening and enhanced treatment regimens for depression could lead to not only better health outcomes but also cost savings compared to "usual care" [29][30][31]. Implementing ADA recommendations and effective interventions demonstrated in the clinical trials could reduce the excess financial burden of MDD among persons with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The ADA recommends depression assessment and treatments into routine diabetes care [3]. Randomized clinical trials have demonstrated that the integrated management of type 2 diabetes and depression could improve both medication adherence and symptoms of diabetes and depression [28], and screening and enhanced treatment regimens for depression could lead to not only better health outcomes but also cost savings compared to "usual care" [29][30][31]. Implementing ADA recommendations and effective interventions demonstrated in the clinical trials could reduce the excess financial burden of MDD among persons with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the IMPACT model has previously been shown to be effective in older populations with diabetes (8), this is the first study to examine a fully integrated program. It is also the first study of IMPACT depression care management in a population of largely Spanish-speaking Latinos.…”
Section: Research Design Andmentioning
confidence: 99%
“…Project Dulce has been shown to improve diabetes outcomes among low-income, predominately Spanish-speaking Latinos with diabetes in San Diego County (6). Similarly, the IMPACT model has been shown to improve depression outcomes (7,8). Our goals were to assess the feasibility of a combined program in a lowincome setting, to demonstrate reductions in depressive symptoms, and to estimate costs of the intervention in a pilot study in three community clinics.…”
mentioning
confidence: 99%
“…Also older patients showed greater cost-offset effects (21,22). Von Korff and colleagues (23) found a costoffset in specialty mental health care for patients with major depression, but not for general medical services. Patients with diabetes and depression who received a stepped collaborative care intervention had greater mental health service costs, but non-mental health medication costs and other outpatient costs were lower.…”
Section: Introductionmentioning
confidence: 99%